Extrinsic Erosion of the Descending Aorta by a Vertebral Fixator - Sokolić, Josip (1991)
We report a rare case in which mechanical extrinsic erosion of the descending thoracic aorta resulted in perforation and periaortic hematoma formation in a 16-year-old girl. Five months before admission to our clinic, the patient had undergone surgical spondylosyndesis with inner vertebral fixation, for the correction of scoliosis. Subsequently, a screw on the fixator became loose, eroding and eventually perforating the wall of the descending aorta. The resultant lesion was at first misdiagnosed as a paravertebral abscess; extrinsic perforation of the descending aorta was suspected prior to operation, but was confirmed only upon surgical exploration. After evacuation of the hematoma, the 1.5-cm aortic perforation was closed directly with continuous sutures. Seven months later, the patient continues to do well. (Texas Heart Institute Journal 1991;18:136-9)